Study of The Effects of Charismatic Leadership Communication and Transparent Communication on Openness to Change with Trust in Organization Mediation Effects (Study at The Ministry of National Development Planning/Bappenas) - Siti Namira Aisyah; Elok Savitri Pusparini (Universitas Negeri Semarang, 2023)
The aim of this study is to examine the effect of charismatic leadership communication and transparent communication in influencing openness to change through the mediating effect of trust in organization. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) to check the fit of the entire model and test causality between constructs. A total of 290 civil servants at the Ministry of National Development Planning/Bappenas participated as research samples. The results of this study reveal that charismatic leadership communication and transparent communication have a positive effect on openness to change, both directly and partially through mediation of trust in the organization. Furthermore, this study is expected to contribute to the organization to encourage the role of good communication carried out by leaders and organizations in a transparent manner to increase employee confidence in the organization, which in turn creates openness to change, especially in the public sector.